Exploration of Ethnomathematics and Philosophical Meaning of Karo Garista Traditional Houses in North Sumatra - Nisa, Khairidatun; Hasibuan, Eka Khairani (JMPM: Jurnal Matematika dan Pendidikan Matematika, 2025)
This study aims to determine ethnomathematics of the roof and ornaments as well as the philosophical meaning contained in the Karo Garista Traditional House in North Sumatra. The research method used in this study is qualitative with an ethnographic approach. Data collection techniques were obtained through observation, interviews, and documentation. The results of the study indicate that there are mathematical concepts in the Karo Garista traditional house, namely, 1) On the roof of the house there are concepts of flat shapes, namely trapezoids and triangles 2) In the ornaments of the house there are concepts of geometric shapes and transformations, namely translation, reflection, rhombus and circle 3) In the philosophical meaning there are mathematical concepts, namely sets, ratios and folding symmetry through spatial layout, number of kitchens, and ornamental patterns full of symbolic meaning. This study provides empirical evidence in cultural preservation, development of culture-based mathematics learning, and enrich ethnomathematics studies in Indonesia.